Assessment of nurses' knowledge towards signs of gross motor delay for children at Alhawija District in Kirkuk Governorate - mohammed, mohammed; ali, ekbal (Iraqi National Journal of Nursing Specialties, 2012)
Background: the early identification of developmental disabilities allows intervention at the earliest possible point toimprove the developmental potential.Objective: Identify the scope of knowledge of nurses toward signs of gross motor delay for children and its relation totheir demographic characteristics.Methodology: A descriptive study design was conducted at (18) primary health care centers in first of the primaryhealth care sector of Alhawija District in Kirkuk Governorate. This study started from September 2010 to the end ofJanuary 2011, in order to identify the level of nurses' knowledge toward signs of gross motor delay for children inprimary health care centers. Non probability (purposive) sample of 20 nurses selected from (18) primary health carecenters. Data were gathered by the investigators who interviewed nurses in their Primary Health Care Centers andfilled out the constructed questionnaire a format which was designed for the purpose of the study. Reliability andvalidity of this tool is determined through application of a pilot study and panel of experts. Data were analyzedthrough the application of descriptive statistical (frequencies and percentages).Results: The findings revealed that the nurses' knowledge in general was poor concerning nurses knowledge aboutsigns of gross motor delay for children, and there is no a relationship between nurses' knowledge and theirdemographic characteristics (age, educational level, years of employment and type of their primary health carecenters).Recommendations: The study recommended that the collaborating work with the Ministry of Health would be helpfulin improving nurses’ knowledge toward detecting of the signs of gross motor delay for children in primary health carecenters through the application of an educational program.